Neonatal and infant immunity for tuberculosis vaccine development: importance of age-matched animal models - Laylaa Ramos; Joan K. Lunney; Mercedes Gonzalez-Juarrero (The Company of Biologists, 2020)
Neonatal and infant immunity differs from that of adults in both the innate and adaptive arms, which are critical contributors to immune-mediated clearance of infection and memory responses elicited during vaccination. The tuberculosis (TB) research community has openly admitted to a vacuum of knowledge about neonatal and infant immune responses to Mycobacterium tuberculosis (Mtb) infection, especially in the functional and phenotypic attributes of memory T cell responses elicited by the only available vaccine for TB, the Bacillus Calmette-Guérin (BCG) vaccine. Although BCG vaccination has variable efficacy in preventing pulmonary TB during adolescence and adulthood, 80% of endemic TB countries still administer BCG at birth because it has a good safety profile and protects children from severe forms of TB. As such, new vaccines must work in conjunction with BCG at birth and, thus, it is essential to understand how BCG shapes the immune system during the first months of life. However, many aspects of the neonatal and infant immune response elicited by vaccination with BCG remain unknown, as only a handful of studies have followed BCG responses in infants. Furthermore, most animal models currently used to study TB vaccine candidates rely on adult-aged animals. This presents unique challenges when transitioning to human trials in neonates or infants. In this Review, we focus on vaccine development in the field of TB and compare the relative utility of animal models used thus far to study neonatal and infant immunity. We encourage the development of neonatal animal models for TB, especially the use of pigs.